Possible role of nuclear factor erythroid 2–related factor 2 in the progression of human colon precancerous lesions. Issue 12 (December 2022) - Polimeno, Lorenzo; Viggiani, Maria Teresa; Giorgio, Floriana; Polimeno, Lucrezia; Fratantonio, Deborah; Di Domenico, Marina; Boccellino, Mariarosaria; Ballini, Andrea; Topi, Skender; Di Leo, Alfredo; Santacroce, Luigi; Barone, Michele
Abstract: Background: Increased levels of oxidative stress/cell inflammation contribute to colorectal cancer (CRC) onset. Nuclear factor-erythroid 2-related factor 2 (Nrf2) and its controlled growth factor erv1-like (Gfer) gene regulate redox‐sensitive and anti-inflammatory mechanisms, respectively, which can contribute to promoting cancer development. Aim: We evaluated Nrf2 and Gfer RNA expression and Nrf2 protein expression in colon mucosa in order to establish their possible involvement in the early stage of CRC. Methods: Forty subjects were enrolled after a histological evaluation of their colon biopsies. They included 20 subjects with a sporadic colorectal adenoma (SpCA group) and 20 without precancerous lesions (controls). Biopsy samples were processed for gene expression analysis and protein expression, using Real-time PCR and immunofluorescence confocal microscopy, respectively. Results: Nrf2 and Gfer mRNA expression were significantly reduced (p=0.007 and p<0.003, respectively) in SpCA tissues compared to normal mucosa from controls. Furthermore, immunofluorescence analysis confirmed a relevant reduction of Nrf2 in SpCA tissue compared to normal tissue from controls. Conclusions: Our data confirm the hypothesis that Nrf2 and Gfer expression may be involved in the initial hits contributing to the multistep process of colon carcinogenesis. Further larger studies are needed to confirm if Nrf2 and Gfer are potential risk/prognostic factors for cancer development.